Strategi Pengelolaan Akun Selebgram @Priscaangelina dalam Menciptakan Personal Branding - Budiono, Gabriella Cecilia; Tandaju, Christina (LITERAKOM: Jurnal Literasi dan Komunikasi, 2023)
The widespread use of Instagram social media at this time, makes Instagram one of the most popular social media and makes the term Instagram celebrity (celebgram) appear. Thus, celebgram becomes a job opportunity in the field of promising services. At this time, many celebgrams are popping up on Instagram, therefore celebgrams must manage their accounts in order to create strong personal branding on Instagram in order to survive and remain relevant to compete with other Instagram accounts. Account management is one of the important things in creating strong personal branding on Instagram in order to find the characteristics and uniqueness of a celebgram. Therefore, this study discusses how the @priscaangelina celebrity account management strategy in creating a personal branding. This study uses a constructivist paradigm, with a descriptive qualitative approach. The purpose of this study was to determine the form of @priscaangelina's strategy with the Phenomenological Tradition, Impression Management Theory, and the Concept of Self-Actualization. By using a qualitative approach and data collection techniques in-depth interviews and documentation. The results of the study show that Prisca Angelina's celebgram manages accounts starting from profiles, appearances and uploaded content.